2013
DOI: 10.1055/s-0032-1331149
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Venous Drainage with Vein Stripper for Reversed Pedicled Neurocutaneous Flaps

Abstract: The flaps based on the vascular axis of superficial sensitive cutaneous nerves had gained increased popularity in reconstructive surgery because of such major advantages as preservation of major extremity arteries and avoidance of microsurgical procedures. However, postoperative venous congestion resulting in partial or total necrosis is still a common problem for these flaps. The aim of the current study is to introduce a new method for reducing the postoperative venous congestion of neural island flap with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In total, 33 studies met the inclusion criteria and were subject to quantitative analysis. 12,14,15,18 -47 Only one study had a comparative design 15 ; all others were case-series. Figure 3 shows the flowchart of the search strategy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 33 studies met the inclusion criteria and were subject to quantitative analysis. 12,14,15,18 -47 Only one study had a comparative design 15 ; all others were case-series. Figure 3 shows the flowchart of the search strategy.…”
Section: Resultsmentioning
confidence: 99%
“…15,20,22,27,37,38,43,46,47 Seventeen studies reported the flap area with a mean size of 50.4 ± 28.62 cm 2 . 14,18,19,21,23,26,29 -32,34 -36,39,41,45,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is well known that flaps with arterial insufficiency (ischemia) recover more rapidly than flaps with venous stasis (congestion) when reperfusion is performed, suggesting that the flap is more susceptible to congestive than ischemic stress. 9 , 10 , 11 , 12
Figure 2 The picture shows an harvested gastric tube, and arrows indicate mesenteric veins. The more distal (head side) the gastric tube is, the more dilated the veins are and the darker the gastric tube is.
…”
Section: Discussionmentioning
confidence: 99%
“…12 While using an internal vein stripper can destroy the competency of potentially obstructive valves in the lesser saphenous vein, other techniques have been reported to bypass them altogether. 34 The inclusion of a cuff of gastrocnemius muscle from the deep midline during flap harvest has been reported to improve venous drainage by utilizing musculocutaneous perforators as an additional bypass pathway. 24 Systematic analysis found this method to have a 2.6% total failure and a 5.2% complication rate with no significant improvement compared with the classic flap (p ¼ 0.65 and p ¼ 0.70, respectively).…”
Section: Venous Outflowmentioning
confidence: 99%